The Correlation Between Students’ Personality and Students’ Speaking Ability - Winda Latifa Rahmi; Shalehoddin; Warno Edi (Didaktika: Jurnal Kependidikan, 2025)
Personality traits play an important role in shaping how students communicate, especially in speaking skills. Extroverted learners are often more confident and expressive, while introverted students may face challenges in oral communication. This study aims to examine the correlation between students’ personality and their English-speaking ability. The focus is on 11th-grade students from a Public Islamic Senior High School, with a total sample of 37 students selected through purposive sampling. Two instruments were used to collect the data: a personality questionnaire and a speaking test in the form of a monologue task. Normality tests confirmed that the data were normally distributed. Pearson’s correlation analysis revealed an r value of 0.275 with a p-value of 0.099, indicating no statistically significant relationship between personality traits and speaking ability. However, descriptive statistics showed that students categorized as extroverts tended to have slightly higher average speaking scores than their introvert and ambivert peers. These findings highlight the nuanced role of personality in language performance and suggest the importance of considering learner characteristics in language instruction.